Solutions for local isolated grid with hybrid system including wind turbine interconnection - Huy, Nguyen Duc; Trung, Tran Nam; Dung, Tran Khanh Viet; Quang, Nguyen Phung; Thai, Vo Hong (Petrovietnam Journal, 2013)
The interconnection of distributed energy systems (renewable energies, diesel generators, and hybrid systems etc.) with utility grid has been one of the most important R&D orientations for many years. The majority of the utilities in the world were not conceived to accommodate large-scale distributed energy systems which can cause problems to the utility grid and different solutions have been developed and proposed. However, the hybrid system (wind turbines and diesel generators) with large capacity of wind turbine interconnection to the local isolated electrical grid on an island has not yet gained a comprehensive solution. In this paper, we present the solution for our hybrid system in Phu Quy island - Vietnam, which has 3 wind turbines (3 x 2MW) and 6 diesel units (6 x 0.5MW) interconnected to the local isolated grid (22kV). Our goals are to maximise the penetration of wind power and keep the system stable. Analytical and simulation studies were performed in order to validate the accuracy of the proposed solution. The results were approved by Vietnam Electricity and the solution proposed is currently being used for the stable operation of our hybrid system.